Peran Sekolah Dalam Upaya Menangkal Radikalisme - Rahmawati Rahmawati; Febrian Alwan Bahrudin; Wika Hardika Legiani (Journal of Civic Education, 2023)
In the contemporary millennial era, a pressing concern affecting teenagers in Indonesia pertains to the proliferation of radicalism among students. This study endeavors to explore the pivotal role played by educational institutions, specifically SMP Negeri 3 Serang city, in mitigating the influence of radicalism. It seeks to identify the underlying factors that render students vulnerable to radical ideologies. Employing a qualitative descriptive approach, this research investigates the effectiveness of schools in counteracting radicalism, with a particular focus on citizenship education. The study reveals that teachers impart essential lessons on national unity, emphasizing the importance of fostering a cohesive nation among students. Additionally, the school collaborates with various stakeholders, including law enforcement agencies such as the police, to disseminate information and combat radicalism. Furthermore, this research identifies internal factors, predominantly rooted in family dynamics, and external factors, linked to the students' surrounding environment, as contributors to susceptibility to radicalism among students. It is important to note that this study's scope is limited to a specific secondary school in Serang.